A feasibility randomised controlled trial of pre-operative occupational therapy to optimise recovery for patients undergoing primary total hip replacement for osteoarthritis (PROOF-THR). (February 2016) - Jepson, Paul; Sands, Gina; Beswick, Andrew D; Davis, Edward T; Blom, Ashley W; Sackley, Catherine M
Objective: To assess the feasibility of a pre-operative occupational therapy intervention for patients undergoing primary total hip replacement. Design: Single blinded feasibility randomised controlled trial, with data collection prior to the intervention, and at 4, 12, and 26 weeks following surgery. Setting: Recruitment from two NHS orthopaedic outpatient centres in the West Midlands, UK. Subjects: Patients awaiting primary total hip replacement due to osteoarthritis were recruited. Following pre-operative assessment, patients were individually randomised to intervention or control by a computer-generated block randomisation algorithm stratified by age and centre. Interventions: The intervention group received a pre-surgery home visit by an occupational therapist who discussed expectations, assessed home safety, and provided appropriate adaptive equipment. The control group received treatment as usual. Outcomes: The study assessed the feasibility of recruitment procedures, delivery of the intervention, appropriateness of outcome measures and data collection methods. Health related quality of life and resource use were recorded at 4, 12 and 26 weeks. Results: Forty-four participants were recruited, 21 were randomised to the occupational therapy intervention and 23 to usual care. Analysis of 26 week data included 18 participants in the intervention group and 21 in the control. The intervention was delivered successfully with no withdrawals or crossovers; 5/44 were lost to follow-up with further missing data for participation and resource use. Conclusions: The feasibility study provided the information required to conduct a definitive trial. Burden of assessment would need to be addressed. A total of 219 patients would be required in an efficacy trial.